Latent profile analysis of classroom behavior problems in an American national sample of prekindergarten children. Issue 4 (25th April 2022) - McDermott, Paul A.; Rovine, Michael J.; Gerstner, Clara‐Christina E.; Weiss, Emily M.; Watkins, Marley W.
Abstract: Problematic behaviors impede young children's ability to succeed in the classroom. Examining individual patterns of behavior problems allows researchers to identify profiles of students most in need of support. This study applied latent profile analysis (LPA) among a national sample ( N = 2764) of American prekindergarten children and found six distinct behavior profiles, which differed in the severity and type (underactive vs. overactive) of behavior problems and the classroom contexts in which problem behaviors arose (peer, learning, and teacher contexts). About two‐thirds of children displayed positive behaviors across classroom contexts, performed well on assessments of early academic ability, and maintained positive relationships with their teachers, indicating generally appropriate adjustment to the preschool environment. Yet, 24% of children were classified into three risk profiles as they demonstrated elevated and pervasive underactive or overactive behavior problems in multiple classroom settings. Children with these profiles were deemed the most vulnerable in the sample, as those with underactive problems had the lowest academic proficiency, and those with overactive problems showed the most negative relationships with teachers and parents. Implications for practice are discussed.